The Effect of Psychological Capital on Entrepreneurial Performance in MSME District in Jatinangor District - Ezranta, Zefanya; Lestari Kadiyono, Anissa; Nugraha, Yus (Riviera Publishing, 2023)
MSMEs or Small, Micro and Medium Units are businesses owned by individuals that have an important role both on a national and international scale. This research aims to find out whether there is an influence from Psychological Capital on Entrepreneurial Performance among MSMEs in Jatinangor District. This study examines MSME actors in terms of their psychological capacity, namely Psychological Capital and the performance of MSME actors. The research design carried out is descriptive research with a quantitative non-experimental approach. This study used convenience sampling and was conducted on 145 MSME actors in Jatinangor sub-district using a questionnaire. The measuring instruments used were the Psychological Capital Questionnaire (PCQ-24) and the Entrepreneurial Performance Questionnaire (EPQ). The data analysis method used is the simple linear regression measurement method. Based on the results of the study, Psychological Capital has a positive influence on Entrepreneurial Performance with a value of 53.2% to measure the contribution of the influence of Psychological Capital on Entrepreneurial Performance where this can also indicate that the higher the Psychological Capital of MSME entrepreneurs in Jatinangor sub-district, the higher the performance of the MSME folder.